The impact of morphine treatment on bladder cancer cell proliferation and apoptosis: in vitro studies - Harper, P.; Hald, O.; Lwaleed, B.A.; Kyyaly, A.; Johnston, D.; Cooper, A.J.; Birch, B. (Experimental Oncology, 2018)
Aim: The aim of this study was to determine the effect of morphine on bladder cancer cell proliferation and apoptosis in vitro. Materials and Methods: MTT assay was used to measure percentage growth of RT-112 human bladder cancer cells after 72 hours of morphine/morphine + naloxone treatment. Expression of µ-opioid receptors was assessed by Western blot and finally, apoptotic assay with CellEvent Caspase-3/7 Green Detection Reagent was carried out using confocal microscopy. Results: The MTT assays showed that morphine increased RT-112 cell growth. Naloxone inhibited this growth enhancing effect. Western blot analysis regarding µ-opioid receptor expression in RT-112 cells remains inconclusive. Morphine was also found to decrease the rate of apoptosis of RT-112 cells, an effect which naloxone inhibited. Conclusions: This study provides evidence that morphine, at clinically relevant doses, causes RT-112 bladder cancer cell proliferation, possibly opioid receptor mediated and at least some of this effect might be due to decreased apoptosis. Clinically, this suggests that in patients with bladder cancer, managing pain with morphine might have detrimental consequences on patient outcomes and alternative pain relief should be considered if possible. Key Words: bladder cancer, morphine, cell proliferation, µ-opioid receptor, apoptosis.